"I'd Be A Completely Different Person if I Hadn't Gone to Therapy": A Qualitative Study of Metacognitive Therapy and Recovery Outcomes in Adults with Schizophrenia. Issue 3 (3rd July 2022) - Kukla, Marina; Arellano-Bravo, Carla; Lysaker, Paul H.
Abstract : Objective: Metacognitive oriented treatments are novel therapies designed to address metacognition deficits in schizophrenia, defined as the set of mental activities that allows reflection on oneself and others, and the integration of this knowledge into sophisticated mental representations that guide adaptive responses to life's demands and to the challenges imposed by psychiatric illness. However, little is known about the first-person experiences of engaging in this treatment. Hence, the purpose of this qualitative study was to characterize first-person experiences of recovery outcomes among people with schizophrenia spectrum disorders who take part in metacognitively oriented psychotherapy. Method: A sample of 13 adult veterans with schizophrenia or schizoaffective disorder in an outpatient setting who were receiving one form of individual metacognitively oriented therapy, Metacognitive Reflection and Insight Therapy, for a minimum of 12 months participated in an open-ended interview; 27 questions probed their experiences with therapy and the outcomes and changes they have observed within themselves as a result. Interviews were analyzed using an inductive consensus based approach. Results: Findings indicate that participants observed changes in their lives in five recovery domains: improvements in real world functioning, increased formation of life pursuits, enhanced interpersonal connections, emergence of self compassion, and improved quality of life and wellness. Conclusions: This study sheds further light on first person experiences of people with schizophrenia and adds to the growing body of evidence supporting the use of this form of metacognitively oriented psychotherapy to promote recovery in important life domains.